Thermal and physical properties of briquette fuels from coconut shells and cocoa shells - Mustafa, Sabirin; Ibrahim, Shariff (Universiti Teknologi MARA (UiTM), 2023)
This study explores the production and characterization of biomass briquettes from coconut and cocoa shells, which are abundant agricultural residues in tropical regions. The motivation behind this research was to investigate the feasibility of utilizing these biomass waste streams for fuel through briquetting, promoting renewable energy applications, and waste management. Briquettes were prepared using different ratios of coconut shells, cocoa shells, and starch as a binder. The mixture was moulded into uniform cylinders and dried to remove moisture and solidify the binder. Thermal properties, such as gross calorific values ranging from 15.92 to 18.30 MJ/kg, and physical properties, including proximate composition, bulk density, and shatter resistance, were assessed. Testing revealed volatile matter ranging from 68.20% to 77.36%, ash content from 9.85% to 13.36%, bulk densities of 0.31 to 0.59 g/cm3, and shatter resistance values from 55.55% to 97.53%. Results showed that the briquettes with a 50:50 ratio had the highest calorific value and density, while the 100% coconut shell briquettes exhibited the highest strength. Overall, the biomass briquettes demonstrated thermal and physical qualities suitable for use as renewable solid fuels, with composition significantly influencing their characteristics. Further optimization of formulations tailored to specific applications could enhance the utilization of these agricultural residues.